2001
DOI: 10.1051/0004-6361:20011196
|View full text |Cite
|
Sign up to set email alerts
|

Steps toward interstellar silicate mineralogy

Abstract: Abstract.Crystalline olivines are an important component of silicate dust particles in space. ISO observations revealed the presence of crystalline silicates in comets, protoplanetary accretion disks, and outflows from evolved stars. For the interpretation of astronomical spectra, the relevant material data at a variety of temperatures and over a broad wavelength range, are urgently needed. In contrast to this need, optical properties of the astronomically interesting olivines are scarcely available at present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
231
3

Year Published

2003
2003
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 229 publications
(248 citation statements)
references
References 26 publications
14
231
3
Order By: Relevance
“…Figure 5 shows IR spectra of San Carlos Olivine measured for the Kyoto and Jena samples. The spectral features of the hand-milled sample are similar to that of the Kyoto sample , in which the sample was prepared by hand-milling, while that of the ball-milled sample is similar to that of the Jena sample (Fabian et al 2001), in which the sample was prepared by ball-milling. Consequently, it is highly probable that the difference in the spectra from different laboratories is due to differences in shape and lattice distortion of particles, caused by the different sample preparation methods: the Kyoto samples are irregular particles with less crystal lattice distortion, while the Jena samples are rounded particles with large lattice distortion.…”
Section: Difference In Spectra By Different Laboratoriesmentioning
confidence: 65%
See 2 more Smart Citations
“…Figure 5 shows IR spectra of San Carlos Olivine measured for the Kyoto and Jena samples. The spectral features of the hand-milled sample are similar to that of the Kyoto sample , in which the sample was prepared by hand-milling, while that of the ball-milled sample is similar to that of the Jena sample (Fabian et al 2001), in which the sample was prepared by ball-milling. Consequently, it is highly probable that the difference in the spectra from different laboratories is due to differences in shape and lattice distortion of particles, caused by the different sample preparation methods: the Kyoto samples are irregular particles with less crystal lattice distortion, while the Jena samples are rounded particles with large lattice distortion.…”
Section: Difference In Spectra By Different Laboratoriesmentioning
confidence: 65%
“…The difference is about 0.05-0.1 μm for 10, 11.2, and 19.5 μm peaks, and about 0.5 μm for 23 and 33 μm peaks. They suggested that the particle shape of the Jena sample is more spherical than the Kyoto sample, because the peak positions for olivine particles with near-spherical shape are located at shorter wavelengths than those with elongated or flat ellipsoidal shapes, as pointed out by Fabian et al (2001).…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…The spectra of the two classes of particulates differ significantly, as discussed by Tamanai et al (2006bTamanai et al ( , 2009b. Correspondence with astronomically observed infrared dust emission bands has been found to be better in some cases for the roundish shapes, especially for the oxides in AGB star outflows (Tamanai et al 2009b; see also Posch et al 1999;and Fabian et al 2001a), but in other cases better for the irregular shapes, especially for forsterite (Tamanai et al 2006b; see also Molster et al 2002;Fabian et al 2001b). Particle shapes and spectra are shown in Fig.…”
Section: Experimental Spectramentioning
confidence: 78%
“…Mg/(Fe + Mg) > 0.9 (see e.g. Jäger et al 1998;Fabian et al 2001;Koike et al 2003). For amorphous silicates, i.e.…”
Section: Introductionmentioning
confidence: 98%